Cortical development in fetuses with congenital heart defects using an automated brain‐age prediction algorithm. (24th August 2019) - Everwijn, Sheila M. P.; Namburete, Ana I. L.; van Geloven, Nan; Jansen, Fenna A. R.; Papageorghiou, Aris T.; Noble, Alison J.; Teunissen, Aalbertine K. K.; Rozendaal, Lieke; Blom, Nico A.; van Lith, Jan M. M.; Haak, Monique C.
Abstract: Introduction: Congenital heart defects are associated with neurodevelopmental delay. It is hypothesized that fetuses affected by congenital heart defect have altered cerebral oxygen perfusion and are therefore prone to delay in cortical maturation. The aim of this study was to determine the difference in fetal brain age between consecutive congenital heart defect cases and controls in the second and third trimester using ultrasound. Material and methods: Since 2014, we have included 90 isolated severe congenital heart defect cases in the Heart And Neurodevelopment (HAND)‐study. Every 4 weeks, detailed neurosonography was performed in these fetuses, including the recording of a 3D volume of the fetal brain, from 20 weeks onwards. In all, 75 healthy fetuses underwent the same protocol to serve as a control group. The volumes were analyzed by automated age prediction software which determines gestational age by the assessment of cortical maturation. Results: In total, 477 volumes were analyzed using the age prediction software (199 volumes of 90 congenital heart defect cases; 278 volumes of 75 controls). Of these, 16 (3.2%) volume recordings were excluded because of imaging quality. The age distribution was 19‐33 weeks. Mixed model analysis showed that the age predicted by brain maturation was 3 days delayed compared with the control group ( P  = .002). Conclusions: This study shows that fetuses with isolated cases of congenital heart defects show some delay in cortical maturation as compared with healthy control cases. The clinical relevance of this small difference is debatable. This finding was consistent throughout pregnancy and did not progress during the third trimester.